PROBLEMATIKA MENULIS TEKS CERPEN PADA PROSES PEMBELAJARAN SISWA (Jurnal Motivasi Pendidikan dan Bahasa, 2023)
Learning is a process of interaction between students and educators who are members of opportunities for students to develop their potential so that all their potential can develop to the fullest. Through learning, students will acquire knowledge, skills, and character attitudes. The problem is that writing skills are much more difficult and more complicated than other linguistic aspects, namely listening skills, speaking skills, and reading skills. Another obstacle encountered in learning to write short stories comes from students. Students do not like short story writing lessons. This study uses a qualitative approach. This type of research is a case study. Data was collected through document study/literature study and interviews. This study aims to overcome how students experience problems writing short story texts in the learning process. The results and discussion of the research are the Study Case Problems of Learning Short Story Writing in Lhokman, South Aceh by discussing several aspects such as obstacles when teaching both from teacher students and learning, learning solutions and strategies, evaluation in learning, student characteristics, and teacher efforts to overcome differences in learning.